2012
DOI: 10.1111/j.1469-8137.2012.04068.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential daytime and night‐time stomatal behavior in plants from North American deserts

Abstract: Summary• Night-time stomatal conductance (g night ) occurs in many ecosystems, but the g night response to environmental drivers is relatively unknown, especially in deserts.• Here, we conducted a Bayesian analysis of stomatal conductance (g) (N = 5013) from 16 species in the Sonoran, Chihuahuan, Mojave and Great Basin Deserts (North America). We partitioned daytime g (g day ) and g night responses by describing g as a mixture of two extreme (dark vs high light) behaviors.• Significant g night was observed acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 70 publications
6
81
2
Order By: Relevance
“…Recent evidence suggests otherwise. Nocturnal water loss often contributes around 10% of the total transpired water (although it can exceed 25% of the total water loss in some desert plants 7 ). The temporal pattern of nocturnal stomatal conductance (g s ) under non-limiting water supply is often characterized by an initial decline during the first hours after dusk, and a posterior increase that peaks around dawn.…”
Section: On the Persistence Of Memorymentioning
confidence: 99%
“…Recent evidence suggests otherwise. Nocturnal water loss often contributes around 10% of the total transpired water (although it can exceed 25% of the total water loss in some desert plants 7 ). The temporal pattern of nocturnal stomatal conductance (g s ) under non-limiting water supply is often characterized by an initial decline during the first hours after dusk, and a posterior increase that peaks around dawn.…”
Section: On the Persistence Of Memorymentioning
confidence: 99%
“…While high sensitivity to g 1 (the slope between the GPP and TR), as shown by Bauerle and Bowden (2011), was expected, the minimum stomatal conductance (g 0 ) had a greater effect on TR, LUE, and WUE. While g 0 has commonly been assumed to be close to zero with little effect on water fluxes (Caird et al 2007;Zeppel et al 2010), recent studies have shown that g 0 could be higher than previously expected in many ecosystems (Ogle et al 2012) and that its value could change seasonally (Barnard and Bauerle 2013). In a recent study using MAESTRA, it was shown that g 0 had a large effect on TR (Bowden and Bauerle 2008).…”
Section: Parameters Set Constant Across the Standmentioning
confidence: 99%
“…However, there is growing evidence at the leaf and plant scales that incomplete stomatal closure and subsequent transpiration overnight are widespread and significant4. Recent studies estimate that the equivalent to 10–15% of daytime leaf and plant water losses occur overnight4, with values reaching 25–30% in desert and savanna plants56, and with some extreme species reaching higher night-time than daytime transpiration7.…”
mentioning
confidence: 99%